The response of Australian chickens naturally infected with avirulent Newcastle disease virus to challenge with velogenic Newcastle disease virus - Spradbrow, Peter Bryan; Ibrahim, Abdul Latif; Ungku Mohsin, Mohd. Ungku Chulan; Milliken, George A.; Shapcott, R.; Kingston, D. (Australian Veterinary Association, 1980)
Sixty-eight breeder chickens, 4 to 12 months of age, were taken from Australian flocks that had been naturally infected with avirulent Newcastle disease virus (NDV) and transported by air to Malaysia. Nearly all the breeders had haemagglutination inhibition antibodies to NDV, at titres of from 2 to 128. Thirty-two were inoculated intranasally with an Asian, velogenic, viscerotropic strain of NDV and all survived this challenge. Thirty-six were exposed to contact infection with the same velogenic NDV and 2 died of Newcastle disease within 14 days. The levels of haemagglutination inhibition antibodies against NDV increased in the surviving breeders after challenge, reaching 2048 or greater in a few birds. Velogenic NDV was isolated from a cloacal swab from one clinically normal breeder 10 days after challenge by contact. Cloacal swabs taken 7 to 10 days after challenge from another 23 breeders yielded no NDV. Twenty-four broilers, 7 weeks of age, were also transported from Australia to Malaysia. All lacked detectable haemagglutination inhibition antibody to NDV and they were from a flock with no detectable antibody to NDV. Twelve were challenged with velogenic NDV intranasally and 12 were subjected to contact challenge. All broilers died of Newcastle disease within 13 days.